Peran Kepala Sekolah dalam Mengembangkan Lembaga melalui Kurikulum Merdeka - Wathon, A (AS-SABIQUN, 2025)
This study investigates the pivotal role of school principals in advancing educational institutions through the implementation of the Kurikulum Merdeka (Independent Curriculum). It focuses on how principals lead, manage resources, and foster innovation to enhance teaching and learning processes. A qualitative approach was adopted, utilizing in-depth interviews, observations, and document analysis in schools that have implemented the Kurikulum Merdeka. The findings highlight that principals serve as transformational leaders, effectively shaping institutional vision, inspiring teacher collaboration, and engaging stakeholders. They play a critical role in managing changes associated with curriculum implementation, ensuring a smooth transition by providing continuous training and professional development for teachers. Through strategic leadership, principals motivate teachers to embrace innovative teaching strategies, fostering a dynamic and engaging learning environment. The implementation of the Kurikulum Merdeka under principal leadership has demonstrated significant improvements in learning quality. It has cultivated a creative and flexible learning atmosphere, promoting student independence and critical thinking. By prioritizing collaboration and leveraging resources efficiently, principals have successfully aligned institutional goals with the curriculum's objectives. This study underscores the importance of strategic and adaptive leadership in addressing the challenges of curriculum reform. Principals’ ability to lead change and optimize institutional potential is critical in achieving educational excellence. The findings suggest that with effective leadership, schools can maximize the benefits of the Kurikulum Merdeka, creating environments that empower students and support holistic development.